Prescribing pattern of psychotropic drugs used in non-psychiatric patients among outpatient department of two teaching hospitals in Bangladesh (Bangladesh Journal of Pharmacology, 2015)
The objectives were to evaluate the prevalence, pattern and rational of psychotropic drugs prescribing by general physicians in two teaching hospitals in Bangladesh in non-psychiatric patient. 320 patients from Sir Salimullah Medical College Hospitals and 240 patients from Holy Family Red Crescent Medical College Hospitals who visited other than psychiatry ward, received psychotropic drugs between July 2012 to June 2013 were analyzed. The rate of psychotropic drugs prescribing was 8.3% and 11.2% in SSMC and HFRCMCH respectively which was found to increase with increasing age and female patient. Benzodiazepines were the most commonly prescribed drugs followed by antidepressant and psychotropic drugs. The psychotropic drugs use was found more in different physical disorder.